THE ‘SPREAD” OF JUNGLE YELLOW FEVER - Dias de Avila-Pires, Fernando (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
The saga of yellow fever has been recounted by several science historians. It is a chronicle of errors, fight for recognition, historical mis-interpretations, and human experiments that would be unacceptable today. But it is also a record of forecasts that would be later confirmed by sound field work and through laboratory and clinical research. It is also an example of the contribution of local native lore to sound scientific discoveries. In this paper we try to demonstrate how we are advancing towards the natural foci of the jungle cycles of a zoonosis, not the reverse.